Headwater streams contain amounts of heavy metal in an alpine forest in the upper reaches of the Yangtze River - Liang, Ziyi; Wu, Fuzhong; Yang, Wanqin; Zhang, Yu; Wu, Junwei; Yang, Fan (Penerbit Universiti Kebangsaan Malaysia, 2019)
Headwater streams are an essential link in the source and sink dynamics of heavy metals between terrestrial and aquatic ecosystems and are also critically important for downstream ecosystem processes and water quality. However, there is little available information about headwater streams. Therefore, the stream storage and distribution patterns of Cd, Pb, Ni, Cr, Cu, Mn and Zn were investigated in ten headwater streams of an Alpine forest located in the upper Yangtze River during the rainy season. The results indicated that the heavy metal storage per unit area of the investigated streams was as follows: 0.95 mg·m-2 for Cd, 8.36 mg m-2 for Pb, 1.98 mg m-2 for Ni, 136.98 mg m-2 for Cr, 9.29 mg m-2 for Cu, 433.39 mg m-2 for Mn and 29.07 mg m-2 for Zn; while the heavy metal storage per unit area of the catchment was as follows: 1.19 mg hm-2 for Cd, 10.47 mg hm-2 for Pb, 2.48 mg hm-2 for Ni, 171.62 mg hm-2 for Cr, 11.64 mg hm-2 for Cu, 542.99 mg hm-2 for Mn and 36.42 mg hm-2 for Zn. Headwater streams present remarkable potential for contamination, and plant debris from riparian forests may be the most important source of heavy metals, while the stream sediment acts as a significant sink for heavy metals. These results provide new perspectives and data for understanding the ecological links between alpine forests and watersheds.